IMPLEMENTASI KEBIJAKAN PENGADAAN BARANG DAN JASA MELALUI SIPLah DI SEKOLAH DASAR KECAMATAN BUKIT BESTARI KOTA TANJUNGPINANG - Pamilia, Syantika Cahya; Muhammad, Adji Suradji; Okparizan, Okparizan (Jurnal Ilmu Administrasi Negara, 2022)
The policy for acquiring school products and services through SIPLah was chosen by the Ministry of Education and Culture to facilitate procuring goods and services easier for schools. The acquisition of products and services is made online through government aid funds, specifically the Dana BOS, such an effort to identify how funds supplied by the government are used by schools. The purpose of this study is to find out how the procurement of school products and services through SIPLah is being implemented at the Bukit Bestari District Elementary School in Tanjungpinang City, as well as the challenges that schools are facing. The data collection techniques were carried out by observation, interviews, and documentation. The collected data is then analyzed through the processes of data reduction, data presentation, and conclusion drawing. By using the implementation theory by Grindle, the results indicate that of the 9 indicators, 8 of them have been running optimally, while 1 indicator, namely the degree of change to be achieved, had not run optimally. The obstacles faced are (1) the products or services available in Tanjungpinang City are not complete, (2) If the products and services required are outside of Tanjungpinang City, the schools are responsible for the delivery fees, (3) Schools often do not find the products/services they need, (4) The process of procuring products and services through SIPLah is considered longer than conventionally. (5) Technical taxes that must be paid when transacting with SIPLah partners are still causing problems for schools.